Designing Collaborative Technology-based Interventions for Mental Health Management - Lopes, Beatriz Severes (2022)
In addition to the impact on public health, especially after the emergence of the COVID-19 pandemic, mental health problems have been amplified globally, leading to higher levels of anxiety and depression especially among young adults, who are among the most vulnerable populations. Due to the specific social context and newfound challenges surrounding university life, psychological distress affects university students at a disproportional higher rate when compared to the general population. With the increase in requests for university therapy services, digital mental health tools developed in conjunction with in-person therapy offer a pioneering solution for expanding the potential and reach of these services while overcoming socioeconomic, geographical, and educational barriers. This thesis explores the process of collaboratively developing a mobile applica tion named Toolbox for mental well-being self-management alongside the psychology counselling services at the University of Madeira. By exploring providers’ perspectives and concerns, this study highlights how a digital solution designed by clinicians could address daily challenges and facilitate treatment protocols. This study presents the potential a mental health app has for improving clinical interventions in the university environment and helping providers of mental health services. The integration of a mental health platform into therapeutic practices can better inform the clients’ course of treatment, particularly due to the collection and analysis of user behaviour-tracking information. It also encourages users to learn about mental health and develop a closer connection with their psychologists. From a methodological standpoint, it proposes the development of mental health app should be conducted in an adaptable process that accommodates the stakehold ers’ expertise and inputs under a cross-disciplinary approach to developing a digital platform that addresses students’ mental health.